2011
DOI: 10.1136/ard.2011.151050
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, progression and sequence of development of radiographic knee osteoarthritis in a symptomatic population

Abstract: These results suggest a common sequence in the development of radiographic knee OA in symptomatic adults beginning in the PFJ, with subsequent addition and progression of TFJOA. It is proposed that isolated symptomatic PFJOA may be one marker for the future development of TFJOA and a target for the early management of knee OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 30 publications
(31 reference statements)
4
106
2
Order By: Relevance
“…Furthermore, it remains unclear what the acceptability of proprioceptive exercises would be based on those with greater severity of knee OA and associated pain, and older people with greater co-morbidities. Further study to assess this may be warranted given that knee OA is a chronic longer-term condition that therefore affects predominantly older individuals [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it remains unclear what the acceptability of proprioceptive exercises would be based on those with greater severity of knee OA and associated pain, and older people with greater co-morbidities. Further study to assess this may be warranted given that knee OA is a chronic longer-term condition that therefore affects predominantly older individuals [7].…”
Section: Discussionmentioning
confidence: 99%
“…OA is the most common form of arthritis, with osteoarthritis of the knee being a leading cause of functional impairment in the elderly [7]. OA is predicted to be the fourth largest cause of disability by 2020 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies found that early signal inhomogeneities and morphologic lesions in the natural history of knee OA frequently occur at the patella, where the cartilage is thickest and therefore may be most vulnerable and sensitive to early degradation 8 47 52–54. Duncan et al 55 studied early radiographic findings in the patellofemoral joint and proposed that the onset of knee OA follows a common sequence initiating at the patellofemoral joint. Our results lend support to the hypothesis that early biochemical changes in the patella cartilage may precede TFOA.…”
Section: Discussionmentioning
confidence: 99%
“…In a three year study, 24% of patients had radiographic signs of OA in the patellofemoral joint, 4% in the tibiofemoral joint, and 41% in both regions of the knee. 7 With these differences in prevalence of OA, understanding the differences of healthy cartilage and the resilience to injury between different joints can help facilitate the development of OA therapeutics, particularly joint-specific treatments.…”
Section: Introductionmentioning
confidence: 99%